Real estate, neoliberalisation and urban governance in Yaoundé and Douala - (:unkn) unknown (My University, 2024)
Based on the cases of Yaoundé and Douala, this doctoral thesis in urban geography examines the ways in which housing production has been reconfigured in Cameroon, combining field data gathered from interviews, internships in municipal administrations and observations of real estate programs with theoretical literature on urban neoliberalism and the neoliberalization of urban policies. The first part of the manuscript analyzes the growing importance of private actors and market logics in the field of residential real estate over the past twenty years. It begins with a genealogy of public housing policies in Cameroon, to identify the times and forms of the redeployment of public action in the field of urban housing. It examines how this redeployment fits in with the global dynamic of neoliberalization and contributes to the ongoing construction of the Cameroonian state. The second part outlines the actually existing neoliberalization in Cameroon's political, economic and social context. It discusses some of its features - the scalar recalibration of public action, then financialization - and concludes with the specifically spatial effects of the recomposition of governance and the new modes of production of residential real estate in the two Cameroonian cities studied. This thesis aims to contribute to the debate on new dynamics in the production of housing and urban spaces in sub-Saharan African cities, and to studies on the neoliberalization of public policies in authoritarian contexts.
Keywords: African Research